2016
DOI: 10.18632/oncotarget.7882
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of USP39 predicts poor prognosis and promotes tumorigenesis of prostate cancer via promoting EGFR mRNA maturation and transcription elongation

Abstract: Castration resistance is a serious problem facing clinical treatment of prostate cancer (PCa). The underlying molecular mechanisms of acquired proliferation ability of tumor cells upon androgen deprivation are largely undetermined. In the present study, we identified that ubiquitin specific peptidase 39 (USP39) was significantly upregulated in PCa samples and cell lines. Elevated USP39 expression was positively correlated with Gleason score, predicted a poor outcome, and functioned as an independent risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 25 publications
2
46
0
Order By: Relevance
“…. These results were also in agreement with the role of USP39, and also belongs to the USPs family in tumour progression, such as hepatocellular carcinoma and prostate cancer . However, further investigation was still needed to confirm whether this well‐characterized DUB activity of USP32 knockdown altered cell cycle and apoptosis regulatory‐related proteins via direct transcriptional or post‐translational regulation in the cell proliferation machinery of SCLC cells.…”
Section: Discussionsupporting
confidence: 81%
“…. These results were also in agreement with the role of USP39, and also belongs to the USPs family in tumour progression, such as hepatocellular carcinoma and prostate cancer . However, further investigation was still needed to confirm whether this well‐characterized DUB activity of USP32 knockdown altered cell cycle and apoptosis regulatory‐related proteins via direct transcriptional or post‐translational regulation in the cell proliferation machinery of SCLC cells.…”
Section: Discussionsupporting
confidence: 81%
“…DUBs catalyse the removal of ubiquitin and polyubiquitin chains from the target protein (8). Ubiquitin-specific proteases (USPs) constitute the largest subgroup of DUBs and are involved in the development of many cancers by upregulating various key oncoproteins (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, USP39 mutation in breast cancer cells, also implicate it as an oncogenic factor, and its downregulation induced apoptosis of the MCF-7 breast tumor cells (9). A study (10) has further demonstrated that USP39 overexpression enhanced the proliferation of prostate cancer cells, thereby suggesting that USP39 may also play a key role in prostate cancer development. All these studies have emphasized that USP39 may be a potential molecular target of cancer.…”
Section: Introductionmentioning
confidence: 92%